(untitled) (Stato, Chiese e pluralismo confessionale, 2018)
SOMMARIO: 1. Annotazioni preliminari - 2. Complessità sociale e complessità giuridica - 3. Modalità alternative di composizione delle controversie - 4. Dal diritto imposto (Ge-setz) al diritto mediato e/o partecipativo - 5. Complementarità fra sostegno politico dei diritti e mediazione dialogica delle fedi - 6. Le (non facili) condizioni di praticabilità del modello di complementarità/distinzione - 7. L’irriducibilità della sfera religioso-fideistica alla sfera politica - 8. Alcune clausole di salvaguardia per le prospettive avvenire. Mediation and Religions: the challenge in a complex society ABSTRACT: Globalization makes social relations increasingly complex, because it favors the introduction and the spread in the same sphere of a plurality of cultures that are often difficult to combine. The proper task of law, that is the one of regulating the cohabitation of people in an equitable manner, is harder in this context, but it can be enhanced with the help of the mediation carried out by religious communities, though the criterion of complementarity/distinction between the order of political conventions and the order of religious convictions is respected.